A sine-wave-shaped skin incision for inserting deep-brain stimulators - ZİYAL, MUSTAFA İBRAHİM; BAYRİ, YAŞAR (SPRINGER WIEN, 2014)
The sine-wave-shaped skin incision is a technique that minimizes skin-related complications near burr hole caps after electrode placement for deep-brain stimulation (DBS). Between 2011 and 2013, 54 DBS electrodes were implanted in 27 consecutive patients with Parkinson's disease (PD), essential tremor, or dystonia. The sine-wave incision was used in 26 patients and conventional bilateral linear scalp incisions were used in one patient. None of the patients whose operations involved sine-wave-shaped incisions developed hardware-linked complications such as skin infection or skin erosion. The one patient who underwent conventional bilateral linear scalp incisions developed a skin infection. By preserving the vascular anatomy of the scalp and reducing skin tension at the wound site, the sine-wave-shaped incision promotes wound healing.
Keywords: Deep-brain stimulation; Scalp incision; Neurosurgery; Surgical technique; Wound healing; HARDWARE-RELATED COMPLICATIONS; SURGERY; WEIGHT; SCALP